Organocatalytic sequential alpha-amination-horner-wadsworth-emmons olefination of aldehydes: enantioselective synthesis of gamma-amino-alpha,beta-unsaturated esters - Kotkar, Shriram P.; Chavan, Vilas B.; Sudalai, Arumugam (Organic Letters, 2007)
A novel and highly enantioselective method for the synthesis of gamma-amino-alpha,beta-unsaturated esters via tandem alpha-amination-Horner-Wadsworth-Emmons (HWE) olefination of aldehydes is described. The one-pot assembly has been demonstrated for the construction of functionalized chiral 2-pyrrolidones, subunits present in several alkaloids.